Drake Strait / Publication of the Office of the Chief of Hydographic Service of the Navy (USSR) - United States. Hydrographic Office (Washington, DC : U.S. Navy Hydrographic Office, 1959)
1st ed., May 26, 1951. Reproduced by the U.S. Navy Hydrographic Office (November 1959) from U.S.S.R. chart Relief shown by hachures, form lines and spot heights. Depths shown by soundings and isolines.; Map in Russian and English.; "U.S.S.R. 169" -- margins Grayscale; 1:3,500,000